2013
DOI: 10.1590/s1516-635x2013000300013
|View full text |Cite
|
Sign up to set email alerts
|

Implications of the use of sorghum in broiler production

Abstract: This study aimed at evaluating total or partial replacement of corn by sorghum in broiler diets and at estimating the effect of the pigment supplementation on broiler performance, carcass and cuts yield, and possible breast and leg pigmentation. We used 1680 one-d-old Ross® 308 broilers. Birds were sexed and distributed according to a completely randomized design (2 x 3 + 1). Treatments consisted of a control diet based on corn and diets with two levels corn replacement by sorghum (50 and 100%) and three pigme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 12 publications
1
9
0
4
Order By: Relevance
“…The results of our study are consistent with previous reports of others (Garcia et al, 2013;Torres et al, 2013;Stringhini et al, 2009;Rocha et al, 2008;Santos et al, 2006) who did not find any differences in feed intake, weight gain or feed conversion when evaluating the growth performance of broilers fed sorghum as partial corn replacement in diets. Zarghi and Golian, (2009) also, revealed that 50% corn replacement with triticale had no negative effect on broiler growth performance.…”
Section: Growth Performancesupporting
confidence: 93%
See 1 more Smart Citation
“…The results of our study are consistent with previous reports of others (Garcia et al, 2013;Torres et al, 2013;Stringhini et al, 2009;Rocha et al, 2008;Santos et al, 2006) who did not find any differences in feed intake, weight gain or feed conversion when evaluating the growth performance of broilers fed sorghum as partial corn replacement in diets. Zarghi and Golian, (2009) also, revealed that 50% corn replacement with triticale had no negative effect on broiler growth performance.…”
Section: Growth Performancesupporting
confidence: 93%
“…The pH values obtained were in the normal limits for this parameter (5.7-5.96 for breast and 6.0-6.2 for thigh meat; Fletcher et al, (2000). Similarly, Garcia et al, (2013) reported that partial substitution of corn by sorghum in the diet did not influence breast and thigh meat pH values.…”
Section: Muscle Phmentioning
confidence: 93%
“…Corn is the main energetic ingredient in diets for birds, and its price rises in the off-season, so sorghum is generally used as a corn substitute. However, sorghum is low in pigments (Laganá, Pizzolante, Turco, Moraes, & Saldanha, 2012;Garcia et al, 2013), making necessary an artificial pigment inclusion in rations. Although the pigment content in PPF was not very high, it was sufficient to increase the yolk colour.…”
Section: Acta Scientiarum Animal Sciencesmentioning
confidence: 99%
“…According to Carolino et al (2014), among the researched options, the one that most closely matches the nutritional characteristics of the corn is sorghum (Sorghum bicolor, L. Moench). The cost of the sorghum grain is between 70% and 80% of corn grain and technically can replace up to 100% of corn in broilers (Fernandes et al, 2002;Garcia et al, 2005;Rocha et al, 2008;Garcia et al, 2013) and layers (Moreno et al, 2007;Assuena et al, 2008) diets, not affecting performance.…”
Section: Introductionmentioning
confidence: 99%